SOSIALISASI PAKAN ALTERNATIF BERBASIS TEPUNG MAGGOT SEBAGAI SUMBER PROTEIN UNGGAS DI DESA MOROME KECAMATAN KONDA KABUPATEN KONAWE SELATAN - Auza, Fuji Astuty; Purwanti, Sri; Syamsu, Jasmal A.; Bain, Ali; Badaruddin, Rusli; Prasanjaya, Putu Nara Kusuma; Kimestri, Asma Bio (BAKIRA: Jurnal Pengabdian Kepada Masyarakat, 2025)
The high and fluctuating cost of poultry feed has become a major constraint for smallholder farmers in Morome Village, Konda Subdistrict, South Konawe Regency. This condition undermines the sustainability of poultry farming and reduces farmers’ profit margins. One potential solution is the utilization of maggot (Hermetia illucens / Black Soldier Fly) meal as an alternative protein source that is environmentally friendly, economically viable, and can be locally produced from organic waste. This community service program aimed to enhance farmers’ knowledge and skills regarding maggot farming, processing into meal, and formulating alternative poultry feed. The implementation methods included participatory observation, interactive lectures through presentations, leaflets, and videos, followed by demonstrations and hands-on training on maggot farming and meal processing. The results showed that participants’ understanding of maggot as poultry feed increased, along with their technical skills in maggot cultivation and processing. Farmers also became more motivated to utilize organic waste as maggot rearing media. Strong enthusiasm was evident through active participation in practice sessions and group discussions. Therefore, this program successfully promoted the adoption of maggot-based alternative feed innovation, supporting both cost efficiency in poultry production and sustainable waste management.